Development of an electric active rollcontrol (ARC) algorithm for a SUV - Jeon, K.; Hwang, H.; Choi, S.; Kim, J.; Jang, K.; Yi, K. (International journal of automotive technology, 2012)
Cornering maneuvers with reduced body roll and without loss in comfort are leading requirements for car manufacturers. An electric active roll control (ARC) system controls body roll angle with motor-driven actuators installed in the centers of the front and rear stabilizer bars. A vehicle analysis model developed using a CarSim S/W was validated using vehicle test data. Two ARC algorithms for a sports utility vehicle (SUV) were designed using a sliding-mode control algorithm based on a nonlinear roll model and an estimated lateral acceleration based on a linearized roll model. Co-simulation with the Matlab simulink controller model and the CarSim vehicle model were conducted to evaluate the performance of two ARC control algorithms. To validate the ARC performance in a real vehicle, vehicle tests were conducted at KATECH proving ground using a small SUV equipped with two ARC actuators, upper and lower controllers and a few subsystems. From the simulation and vehicle validation test results, the proposed ARC control algorithm for the developed ARC actuator prototypes improves the vehicle’s dynamic performance.